Development of a Prototype Integrated Library System (ILS) for selected public high school libraries in Quezon City Angelie T. Dela Cruz, Mark Elizier T. Pineda ; Dan Anthony D. Dorado, adviser. - Dela Cruz, Angelie T.; Pineda, Mark Elizier T. (2013)
The paper presents the development of a prototype Integrated Library System for selected public high school libraries in Quezon City. The ILS aims to provide a faster and more efficient alternative to the existing system in the public high school libraries. Design and specific functions incorporated in the ILS were based from the assessed needs of library users and library administrators in the preliminary study conducted in six public high schools in Quezon City. Based from the preliminary study, an ILS for the selected public high schools was developed. The modules that were identified from the preliminary study and created for the system, were Cataloging, Circulation, Online Public Access Catalog, Acquisition, User Management, and System Management.